SIGNIFICANCE OF NEW NON-PLASTER TECHNOLOGIES OF EARLY PRIMARY PROSTHETICS AS AN INEQUITABLE PART OF MEDICAL REHABILITATION OF DISABLED PEOPLE AFTER BELOW-AND ABOVE KNEE AMPUTATION - Вадим Геннадьевич Сусляев; Людмила Михайловна Смирнова (Медицина в Кузбассе, 2018)
Subject. Primary prosthesis of patients after below-and above knee amputation.